Anticytomegalovirus Peptides Point to New Insights for CMV Entry Mechanisms and the Limitations of In Vitro Screenings - Joseph W. Jackson (American Society for Microbiology, 2019)
ABSTRACT Human cytomegalovirus (HCMV) is a ubiquitous betaherpesvirus that can cause severe disease following in utero exposure, during primary infection, or latent virus reactivation in immunocompromised populations. These complications lead to a 1- to 2-billion-dollar economic burden, making vaccine development and/or alternative treatments a high priority. Current treatments for HCMV include nucleoside analogues such as ganciclovir (GCV), foscarnet, and cidofovir. Recently, letermovir, a terminase complex inhibitor, was approved for prophylaxis after stem cell transplantation. These treatments have unwanted side effects, and HCMV is becoming resistant to them. Therefore, we sought to develop an alternative treatment that targets a different stage in viral infection. Currently, small antiviral peptides are being investigated as anti-influenza and anti-HIV treatments. We have developed heparan sulfate-binding peptides as tools for preventing CMV infections. These peptides are highly effective at stopping infection of fibroblasts with in vitro-derived HCMV and murine cytomegalovirus (MCMV). However, they do not prevent MCMV infection in vivo. Interestingly, these peptides inhibit infectivity of in vivo-derived CMVs, albeit not as well as tissue culture-grown CMVs. We further demonstrate that this class of heparan sulfate-binding peptides is incapable of inhibiting MCMV cell-to-cell spread, which is independent of heparan sulfate usage. These data indicate that inhibition of CMV infection can be achieved using synthetic polybasic peptides, but cell-to-cell spread and in vivo-grown CMVs require further investigation to design appropriate anti-CMV peptides. IMPORTANCE In the absence of an effective vaccine to prevent HCMV infections, alternative interventions must be developed. Prevention of viral entry into susceptible cells is an attractive alternative strategy. Here we report that heparan sulfate-binding peptides effectively inhibit entry into fibroblasts of in vitro-derived CMVs and partially inhibit in vivo-derived CMVs. This includes the inhibition of urine-derived HCMV (uCMV), which is highly resistant to antibody neutralization. While these antiviral peptides are highly effective at inhibiting cell-free virus, they do not inhibit MCMV cell-to-cell spread. This underscores the need to understand the mechanism of cell-to-cell spread and differences between in vivo-derived versus in vitro-derived CMV entry to effectively prevent CMV’s spread.